Effects of ethyl palmitate on the release of aroma compounds in propanediol–ethanol solution and its mechanisms - Guo, Wei-Wei; Luo, Li-Wen; Wang, Ding-Zhong; Fu, Ying-Jie; Xi, Hui; Sun, Shi-Hao (Frontiers in Chemistry, 2024)
Long-chain esters (LCEs) are known to affect aroma perception, but the mechanism of their effects remains unclear. In this study, ethyl palmitate (EP), an important LCE in Osmanthus fragrans flower absolute (OFFA), was selected as a target to identify its role and mechanism. The release characteristics of 10 aroma compounds from OFFA with and without EP were obtained by headspace gas chromatography mass spectrometry (HS-GC/MS) and olfactometry evaluation, respectively. The results show that EP changes the release behaviors of volatile compounds in solution, increases their olfactory detection thresholds (ODTs), and reduces the equilibrium headspace concentrations. According to Whitman’s two-film model, EP was found to change the partition coefficients and mass transfer coefficients of the compounds between the liquid and gas phases. This indicates that EP plays an important role in the scent formation of a flavor product and that it is very valuable for the style design of the flavor product.